Injury prevention training in girls´and women´s elite football in Denmark: A survey of practices and perceptions - Bandak, E.; Zebis, M.; Alkjaer, T.; Nielsen, S. M.; Bennike, S.; Thorborg, K. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Through a national cross-sectional survey, the present study investigated the use and content of injury prevention training (IPT), and associated attitudes and beliefs, involving stakeholders in Danish girls' and women's elite football (U14, U16, U18, and Danish Women's League teams). A total of 168 stakeholders (coaches, physical performance coaches, physiotherapists, medical doctors, and club management) from 18 Danish elite clubs were invited to participate. Of these, 158 were eligible to participate, and 110 participants (69.6% response rate) provided 191 valid survey responses, as some provided more than one response due to multiple affiliations within the same club. The use of IPT ranged from 91.1% to 100% across team levels, with approximately 50% reporting up to 1-2 h/week. Interestingly, only 52.9%-72.7% of the responses indicated use of an evidence-based IPT program, with lowest adoption at the U14 and Danish Women's League teams. The FIFA 11+ was the most used evidence-based IPT program. The majority of the participants (>72%) had positive perceptions regarding IPT impact on injury reduction. These findings indicate that, while IPT is broadly used across Danish girls' and women's elite football teams, the implementation of evidence-based IPT programs varies, with lower adoption of these programs among the youngest and senior elite teams. Hence, there is a need to enhance integration of IPT programs proven effective in girls' and women's elite football. Notably, stakeholders expressed positive perceptions regarding the impact of IPT on injury reduction, which provides valuable support for future efforts to strengthen IPT in football practice.